Draft Eleventh Five Year Plan (2007-2012) and Annual Plan (2007-2008) Volume-III - Planning Commission (Planning Commission, 2007)
A natural conglomeration of beauty and grace, Assam Hill Areas comprises two districts - viz., North Cachar Hills and Karbi Anglong, which are largely inhabited by various tribes like Karbi, Dimasa, Jeme, Nagas, Kuki, Hmar, Bodo, Syam, Hrangkhol, Khasi etc. The total geographical are of the two hill districts is 15,322 sq.km. which accounts 19.53% of the geographical area of the State of Assam. Situated between Brahmaputra Valley on the North and Barak valley on the South, which is bisected by Nagaland on the East, Meghalaya on the South the two districts combine Sub-Himalayan ranges in the form of Barail tract having altitude of about 1800 meters from sea level. The Hill ranges provide moderate climate through out the year whereas plain areas have moist and warm climate. The Hill district population is 9.98 lakhs, out of which Karbi Anglong has 8.12 lakhs and N.C. Hills has 1.86 lakhs. Literacy percentage for the Hill Areas is 63.71%. There are 5 Sub-divisions, 16 Blocks, 10 Revenue Circles in the Hill Areas of Assam
Planning and Development Department Government of Assam